Neutrophil-Mediated Gastrointestinal Injury - Susan N Elliott; John L Wallace (Canadian Journal of Gastroenterology)
Inflammatory diseases of the gastrointestinal tract are frequently characterized by a dense infiltration of neutrophils in the lamina propria and the subsequent transepithelial migration of these cells into the lumen. While the neutrophil plays an essential role in defending against bacterial infection, it can also cause significant injury to the host tissue. The evidence for a role of neutrophils in producing significant tissue injury in a number of gastrointestinal disorders and the mechanisms through which neutrophils produce tissue injury are reviewed. Furthermore, the evidence that some commonly used anti-inflammatory drugs produce beneficial effects through modulation of neutrophil extravasation or activation is reviewed.